SEE! Urban transformation in Southeastern Europe. - (:unkn) unknown (Lit, 2012)
Can we, by drawing on the experience of different independent initiatives and associations in Southeastern Europe, draft and collate typical development and qualification strategies for periods of urban transformation and post-conflict situations, and apply them to similar urban situations elsewhere? The publication presents different approaches to this topic and answers the question with yes! The publication on the Archis SEE Network specifically presents contributions from local initiatives throughout the region and looks forward to enhancing debate and action, with both local and international impact. In cooperation with local initiatives launched by architects, planners, artists, urbanists, sociologists and other professionals engaged in the process of improving various political and social dimensions of the urban environment, Archis Interventions has established a network in Southeastern Europe. The network fosters the exchange of knowledge and best practices in order to integrate the issue discussed in international discourse on urbanism, and to support local initiatives.
Keywords: Stadtentwicklungsplanung; Stadtplanung; Städtebau; Stadtwachstum; Urbanität; Architektur; Sozialwandel; Raumentwicklung; Flächennutzung; Zersiedelung; Bevölkerungswanderung; Suburbanisierung; Migration; Transformation; Informelle Siedlung; Globalisierung; Urban Sprawl